Internationalization, Digitalization And Sustainability Development UMKM Woven Bag Products In Ngawi District - Heny Sidanti (Publisher Cv. Inara, 2021)
In times like this, MSMEs have a lot of limitations in developing the business of Internationalization, Digitalization and Sustainability even though MSME players have developed internationalization by serving domestic and foreign demand as has been done by MSMEs woven bag products in Kab. Ngawi. The purpose of this study was to determine the strategies that have been carried out by the woven bag UMKM actors in the district. Ngawi in the development of internationalization, digitization, and sustainability which may not be done by other MSME actors sometimes.This study finds that in carrying out international development, product innovations are needed especially during the current Covid-19 pandemic to be able to help the continuity of a company or MSME business, as well as the role of digitalization which is a very vital technology that must be applied every time it does development through social media such as Facebook, IG, WA, Promotion, and others, as well as the sustainability of a relationship in doing business and products, must be maintained.